Depression and anxiety in peruvian military personnel during the pandemic context: a cross-sectional study - Mario J. Valladares-Garrido; Cinthia Karina Picón-Reátegui; J. Pierre Zila-Velasque; Pamela Grados-Espinoza; Víctor J. Vera-Ponce; César Johan Pereira-Victorio; Danai Valladares-Garrido; Virgilio E. Failoc-Rojas (BMC, 2023)
Abstract Background During the COVID-19 pandemic, increased workload and stress could have increased mental health problems (anxiety and depression) in military personnel. However, the number of studies in military members is scarce, especially in regard to mental health. The objective of this study was determine the prevalence and factors associated with depression and anxiety in Peruvian military personnel. Methods We undertook an analytical cross-sectional study. The survey was distributed face to face between November 02 and 09, 2021, during the second wave of the COVID-19 pandemic among the military personnel. We used some instruments to measure depression (Patient Health Questionnaire, PHQ-9), anxiety (Generalized Anxiety Disorder, GAD-7), insomnia (Insomnia Severity Index, ISI), food insecurity (Household Food Insecurity Access Scale, HFIAS), physical activity (International Physical Activity Questionnaires, IPAQ-S), resilience (abbreviated CD-RISC), and fear of COVID-19 scale. The exclusion criteria included those who did not completely fill out the evaluation instruments. Results We analyzed the data of 615 military personnel that participated in the survey. Of them, 93.7% were male and the median age was 22 years old. There was a prevalence of 29.9% and 22.0% in regard to depression and anxiety symptoms, respectively. In addition, it was found that being married (PR: 0.63; 95% IC: 0.42-0.94), having a relative with mental health problems (PR: 2.16), having experienced food insecurity (PR: 1.48), insomnia (PR: 2.71), fear of COVID-19 (PR: 1.48), and a high level of resilience (PR: 0.65) were factors associated with depression. In regard to anxiety, the factors associated were working for more than 18 months since the beginning of the COVID-19 pandemic (PR: 0.52), a high level of resilience (PR: 0.50; 95% IC: 0.33-0.77), insomnia (PR: 3.32), fear of COVID-19 (PR: 2.43). Conclusion We found a prevalence of symptoms of depression and anxiety of 29.9% and 22.0%, respectively. In regard to the factors that attenuate depression, we can mention being married and having resilience; and among the aggravating factors, having a relative with mental health problems, food insecurity, insomnia, and fear of COVID-19. Finally, anxiety increased through working time, insomnia, and fear of COVID-19.